Author Correction: Metformin reverses established lung fibrosis in a bleomycin model. (October 2018) - Rangarajan, Sunad; Bone, Nathaniel; Zmijewska, Anna; Jiang, Shaoning; Park, Dae; Bernard, Karen; Locy, Morgan; Ravi, Saranya; Deshane, Jessy; Mannon, Roslyn; Abraham, Edward; Darley-Usmar, Victor; et al.
In the version of this article originally published, a grant was omitted from the Acknowledgements section. The following sentence should have been included: "R.B.M. was supported by a Department of Veterans Affairs Merit Award (5I01BX003272)." The error has been corrected in the HTML and PDF versions of this article.